Investigations Into the Phenomenology and the Ontology of the Work of Art What are Artworks and How Do We Experience Them? - Bundgaard, Peer F.; Stjernfelt, Frederik (Contributions to Phenomenology, 2015)
​This book investigates the nature of aesthetic experience and aesthetic objects. Written by leading philosophers, psychologists, literary scholars and semioticians, the book addresses two intertwined issues. The first is related to the phenomenology of aesthetic experience: The understanding of how human beings respond to artworks, how we process linguistic or visual information, and what properties in artworks trigger aesthetic experiences. The examination of the properties of aesthetic experience reveals essential aspects of our perceptual, cognitive, and semiotic capacities. The second issue studied in this volume is related to the ontology of the work of art: Written or visual artworks are a specific type of objects, containing particular kinds of representation which elicit a particular kind of experience. The research question explored is: What properties in artful objects trigger this type of experience, and what characterizes representation in written and visual artworks? The volume sets the scene for state-of-the-art inquiries in the intersection between the psychology and ontology of art. The investigations of the relation between the properties of artworks and the characteristics of aesthetic experience increase our insight into what art is. In addition, they shed light on essential properties of human meaning-making in general.